All-inorganic bifacial CsPbBr3 perovskite solar cells with a 98.5%-bifacial factor. Issue 59 (10th July 2018) - Li, Yanan; Duan, Jialong; Zhao, Yuanyuan; Tang, Qunwei
Abstract : A bifacial all-inorganic PSC with a bifacial factor as high as 98.5% is made by sharing a single carbon back-electrode. Abstract : We present here the construction of all-inorganic bifacial CsPbBr3 perovskite solar cells to harvest solar energy from both sides. The quantum dot modified bifacial device achieves front and rear efficiencies of 7.55% and 7.44% under one sun illumination, respectively. The solar cell without encapsulation retains around 95% of the initial efficiency at 60% RH over a period of 1000 h.